Terapi Bekam dalam Menurunkan Intensitas Dismenore dan Tanda-Tanda Vital (Nadi dan Tekanan Darah) - Vania Pangestika Purwaningrum; Ni Ketut Alit Armini; Elida Ulfiana; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2019)
Introduction: Dysmenorrhea made intolerance to work and absence from work or school. This situation made someone to be unproductive. This study was aimed to determine that cupping therapy is effective to reduction the intensity of dysmenorrhea and vital signs (pulse, systolic and diastolic blood pressure).Methods: This type of research was a quasi-experimental design study with the posttest design only design . The population were all of the female students aged 18-23 years who had primary dysmenorrhea. The sampling method was quota sample with 42 samples that divided into experimental group and control group with 21 samples. The independent variable was cupping therapy and the dependent variable was the intensity of dysmenorrhea and vital signs. The instruments used in this study were numeric rating scale, questionnaire sheets and observation sheets. Data analysis used Mann Whitney U Test.Results: The result showed that dysmenorrhea intensity variable had (p=0.000) its means that there are differences in the effectiveness of cupping therapy in the control group to decrease the intensity of symptoms of dysmenorrhea. In the pulse variable the results were (p= 0.596), systole blood pressure (p= 0.213), and diastole (p=0.639) (p>0.05).Conclusion: It can be concluded that, there are differences in effectiveness between groups given cupping therapy with the control group to decrease the intensity of dysmenorrhea, for pulse variables, systolic and diastolic blood pressure there was no difference between the two groups.